Microfiber ingestion in Patagonotothen kreffti from the Namuncurá/Burdwood Bank Marine Protected Area - Ojeda, Mariel Adriana (2025)
Microfibers (MFs) are an anthropogenic pollutant with a major impact on the marine environment. Due to their size, they can be ingested directly (from the environment) or indirectly (with their prey) by organisms. The aim of this study was to analyze and compare the occurrence, abundance and physicochemical characteristics of MFs present in Patagonotothen kreffti from the Marine Protected Area Namuncurá/Burdwood Bank (MPA N/BB) during two seasons: winter and spring. The notothenioids were obtained from the oceanographic surveys of August 2018 and December 2018. Oxidative digestions of fish gastrointestinal tracts were used to recover MFs and further determine the number per individual (MFs ind-1) and per gram of tissue (MFs g-1). Each MF was characterized by total length, color, wear and discoloration, and chemical composition. In winter, P. kreffti presented an occurrence of 100% with values of 5.71 ± 3.19 MFs ind-1 and 1.22 ± 1.45 MFs g-1, while in spring the occurrence was 85.71%, with abundances of 3.71 ± 3.30 MFs ind-1 and 0.28 ± 0.23 MFs g-1, with no significant differences between seasons (Wilcoxon, p > 0.05). The mean size of the MFs was 0.89 mm, and blue MFs were in the majority (57.35%). Wear and discoloration were observed in 42.42% of the MFs. Cellulose MFs were the most abundant followed by polyester MFs. P. kreffti could be used to assess MF contamination in the N/BB MPA because it is endemic and has higher abundances of MFs than other notothenioids in the area.